A Multi-criteria Decision Making Method based on Interval Type-2 Fuzzy Sets for Supplier Selection (Journal of Informatics and Mathematical Sciences, 2017)
Supplier selection is one of the most important activities in supply chain management. The right choice of supplier would help the company to reduce purchasing risk, maximizing the overall profit and increasing customer satisfaction. However, the method of selecting the right supplier is not straightforward as it involves a number of potential companies with diverse conflicting criteria. This paper aims to propose a modified technique for order preference by incorporating the concepts of entropy weight interval type-2 fuzzy sets and linguistic weighted average. The proposed method is illustrated with a problem of supplier selection. The evaluation results using the proposed method are consistent with the original results. This indicates that the proposed method offers a feasible solution to supplier selection problems
Keywords: Supplier selection; Entropy method; Linguistic weighted average; Decision making